Intelligent robust control of high precision positioning systems using ANFIS - Rafaat, Safanah; Martono, Wahyudi; Akmeliawati, Rini; Legowo, Ari (2010)
Modern mechanical systems, such as machine tools, microelectronics manufacturing equipment, are often required to operate in high speed to yield high productivity. At the same time, precision/accuracy requirement becomes more and more stringent because of factors like the reduced size of components in modern mechanical devices or microelectronics products and high-quality surface-finishing requirements. High Precision Positioning System (HPPS) usually requires a good control to satisfy the requirement: robust high accuracy positioning and tracking performance at high speed, fast response with no or small overshoot and robustness to uncertainties. The development of robust control systems for HPPS is an attempt to provide guaranteed stability despite uncertainties and disturbances associated with the plant. However, robust control techniques require a dynamic model of the plant under study and bounds on modeling uncertainty to develop control laws with guaranteed stability. Although identification techniques for modeling dynamic systems and estimating model parameters are well established, very few procedures exist for estimating uncertainty bounds. A conservative bound is usually chosen to ensure robust stability, which will severely affect the high performance requirement of HPPS.